Theories of international relations - Chan, Stephen; Moore, Cerwyn (Sage library of international relations., 2006)
Comprises 80 articles representing the most influential theoretical writings by international relations scholars. Introduced by an essay from Stephen Chan and Cerwyn Moore, the four thematically organised volumes cover the major traditions of IR theory. Together these four volumes provide broad coverage of the subject and historical depth.